Industrial biography iron workers and tool makers - Smiles, Samuel, 1812-1904 (John Murray, 1863)
Following from the author's 'Lives of the Engineers', this accessible work presents the lives of many celebrated inventors, mechanics, and iron-workers - the founders in great measure of the modern industry of Britain.
Includes index.
Keywords: Iron industry and trade -- Great Britain -- Biography.; Industrial arts -- Great Britain -- Biography.; elektronické knihy; electronic books